1999
DOI: 10.1136/bjo.83.2.168
|View full text |Cite
|
Sign up to set email alerts
|

Indocyanine green guided laser photocoagulation in patients with occult choroidal neovascularisation

Abstract: Aims-To determine whether indocyanine green (ICG) guided laser photocoagulation of occult choroidal neovascularisations (OCNV) is beneficial for patients with occult choroidal neovascularisation secondary to age related macular degeneration (AMD). Methods-A prospective pilot study was performed in 21 eyes with OCNV secondary to AMD that could be identified extrafoveolarly or juxtafoveolarly in an early ICG angiographic study. Laser photocoagulation was applied to the neovascular membrane identified in the earl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1999
1999
2005
2005

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Recently, ICG-guided laser photocoagulation has been proposed for patients with occult CNV and a visible capillary network in the early ICG angiograms. It has been suggested that patients benefit from laser photocoagulation of occult CNV which are visible in the early ICG-angiographic study [27]. In our study, only 10 eyes with occult CNV and a distinct capillary network had a juxta-or extrafoveal lesion and were treated by ICGguided laser photocoagulation.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Recently, ICG-guided laser photocoagulation has been proposed for patients with occult CNV and a visible capillary network in the early ICG angiograms. It has been suggested that patients benefit from laser photocoagulation of occult CNV which are visible in the early ICG-angiographic study [27]. In our study, only 10 eyes with occult CNV and a distinct capillary network had a juxta-or extrafoveal lesion and were treated by ICGguided laser photocoagulation.…”
Section: Discussionmentioning
confidence: 88%
“…ICG angiography has been suggested to be a valuable tool in identifying occult CNV and converting them into visible CNV, either as neovascular capillary network in the early-phase angiogram or as plaque-like hyperfluorescence in the late-phase angiogram.. [12,28,29,31]. We were especially interested in the proportion of eyes with a neovascular capillary network in the early-phase angiogram since these eyes may be eligible for laser photocoagulation [27]. In this study we were able to visualize a distinct neovascular network in 50 eyes (29%) of the occult group.…”
Section: Discussionmentioning
confidence: 99%
“…Indications for treatment, visual prognosis, and recurrence rate in these three CNV morphological types are quite diVerent. 2 Furthermore, a marked disproportion between eyes with pigment epithelial detachment (PED) (two cases) and those without PED (the remaining 19), not reflecting the data provided by Guyer and colleagues in 1000 consecutive eyes, 3 characterises the examined population. The authors present the final anatomical and visual outcomes by considering all eyes as a single group; this method is questionable, since vascularised PED and RPE are definitely two distinct entities.…”
Section: F P Larkin Moorfields Eye Hospital London Ec1v 2pdmentioning
confidence: 99%
“…ICG-guided laser photocoagulation has recently been proposed as a new treatment modality for occult CNV in AMD [6,8,9,[24][25][26][27][28]. We conducted a prospective pilot study to evaluate the functional and anatomical results of ICG-guided laser photocoagulation of juxta-and extrafoveal occult CNV appearing as late-phase fluorescein leakage of an undetermined source.…”
Section: Introductionmentioning
confidence: 99%